Cultural Factors Influencing the Incidence of Chronic Energy Deficiency (CED) in Pregnant Women in the Langke Majok Health Center Work Area - Martina Dwi Putri Riberu; Marni Marni; Helga JN Ndun (Fakultas Kesehatan Masyarakat, Universitas Muhammadiyah Palu, 2024)
ntroduction: Nutrition of pregnant women is one of the focuses of attention in improving community nutrition because it has a significant impact on the condition of the fetus. Mothers with risk KEK can have a negative impact on him itself such as anemia, bleeding, the mother's weight is not increase in a way normal and caught disease infection. KEK on Mother pregnant can cause miscarriage, baby born dead, dead in content and disabled carry-on. Case KEK Which happen in Manggarai Regency is caused by many factors, one of which is is the eating culture of pregnant women influenced by culture area local. The research results show that pregnant women's eating practices are carried out because of beliefs and habits in the family. Biological parents encourage mothers to abstain from eating because of the habits and beliefs in the family. Food taboo habits in the family are divided into two, namely food taboos that are carried out because of the habits of the biological family and habits that follow the husband's family after marriage. The husband's parents were also found to be a driving force for the mother to abstain from eating. Community health centers need to provide education regarding dietary restrictions not only to pregnant women but also to families and the community so that the nutritional needs of pregnant women are met. Objective: Study This aiming for describe factor culture that influences the occurrence of KEK in pregnant women in the work area of Langke Majok Health Center, including the eating practices of pregnant women, the role of parents and the eating culture of pregnant women. Method: This type of research is qualitative with an ethnographic research design. The informants consist of informants The key is eight pregnant women with KEK and eight supporting informants, with the instrument used being an interview guideline conducted by means of in-depth interviews, observation and documentation. The data analysis technique used is based on the approach taken by Miles and Huberman by means of data reduction, data presentation and drawing conclusions. Results: Research results shows that mothers' eating practices pregnant done because of beliefs and customs which exists in the family which requires the mother to follow the habit. This is supported by the role of biological parents who require the mother to do food taboos because of the habits and beliefs in the family. In addition to following the habits of biological parents. Food taboos carried out by pregnant women because of the role husband's parents as giver information, because after Marry a wife must follow customs and beliefs who is in the family husband. Culture abstinence Eat Which There is in area local directly not require Mother pregnant for do food taboos, but the belief in the tradition of food taboos that exist in the biological family that is carried out by the mother during her life. In addition, in the tradition of Manggarai culture, when married, the wife follows the customs of the husband's family as a form of respect for her husband, marked by the wife living with her husband's parents. Conclusion: Eating practices are carried out because of beliefs and customs in the family. The role of parents in eating taboos as a provider of information on eating taboos to pregnant women, the culture of fasting at night in the local area does not require pregnant women to carry out eating taboos except to follow the beliefs and traditions that exist in the family.